Medical tourism service quality: finally some empirical findings - Abd. Manaf, Noor Hazilah; Hussin, Husnayati; Jahn Kassim, Puteri Nemie; Alavi, Rokiah; Dahari, Zainurin (Taylor and Francis (Routledge), 2015)
The purpose of this paper is to examine service quality, perceived value, overall satisfaction and future intention among medical tourists who seek treatment in Malaysian private hospitals. Self-administered questionnaire was main method of data collection. Respondents comprised foreign patients who seek medical treatment, and/or related medical services such as tests and medical check-ups. Expatriates and foreign nationals residing in Malaysia were excluded. Altogether 173 responses were received and analysed by SPSS 17. Three dimensions of medical tourism service quality were identified namely medical staff quality, supporting services quality, and administrative services quality. Medical staff quality was found to predict all three variables of patient satisfaction, perceived value and future intention for treatment. Very limited empirical research has been carried out with actual data from patients due to difficulty in getting access to international patients, and patients’ reluctance to participate. This study is among the first few which examines medical tourism service quality with actual patient data. The research identifies important constituents of medical tourism which may assist policy-makers and hospital managers in better understanding the industry.